Pendampingan Usaha Kecil dan Menengah Keripik Basreng AW dalam Peningkatan Penjualan dan Efisiensi Produksi - Rasil, Feryan Hadyan; Wijaya, Hansel; Elsa, Jessica Charis; Michael, Michael; Wijaya, Karen Mirabel; Jeremia, Michael; Mei, Siaw Mei; Saraswati, Dewi (Journal Pemberdayaan Masyarakat Indonesia, 2019)
Community Development Program initiated by Universitas Prasetiya Mulya aims to improve community welfare through the assistance and business development of the partners. In 2019, the Community program was taking place in Cianjur, West Java. One of the business partner assisted and developed in the Community Development 2019 program is the Basreng chips business owned by Kang Wendy. Kang Wendy sells and market the product under a brand called AW Basreng. Kang Wendy encounters some challenges in developing his business due to lack of knowledge and skill in managing a good business. However, the Basreng chips business has the potential to develop and can be sustainable because of the characteristic the Basreng flavor developed by Kang Wendy. Within the 45 days, Kang Wendy and the builder team had made some improvements in the area of operational management, marketing, human resources, and finance. With regards to the improvement, Kang Wendy's most successfully achievement is accelerating the production process time and expanding product marketing through online marketing. The writing of this article aims to provide an overview of the problems that arise in MSME businesses and the corrective steps that can be taken to develop a Basreng business in Cianjur, West Java.